One‐step zymogram method for the simultaneous detection of cellulase/xylanase activity and molecular weight estimation of the enzyme. Issue 3 (22nd November 2016) - Cano‐Ramírez, Claudia; Santiago‐Hernández, Alejandro; Rivera‐Orduña, Flor Nohemí; Pineda‐Mendoza, Rosa María; Zúñiga, Gerardo; Hidalgo‐Lara, María Eugenia
Abstract : Here, we describe a zymographic method for the simultaneous detection of enzymatic activity and molecular weight (MW) estimation, following a single electrophoresis step. This involved separating cellulase and xylanase activities from bacteria and fungi, obtained from different sources, such as commercial extracts, crude extract and purified proteins, under denaturing conditions, by 10% polyacrylamide gel electrophoresis, using polyacrylamide gels copolymerized with 1% (w/v) carboxymethylcellulose or beechwood xylan as substrates. Then, enzymes were refolded by treatment with 2.5% Triton X‐100 in an appropriate buffer for each enzymatic activity, and visualized by Coomassie blue staining for MW estimation. Finally, Congo red staining revealed bio‐active cellulase and xylanase bands after electrophoretic separation of the proteins in the preparations. This method may provide a useful additional tool for screening of particular cellulase and xylanase producers, identification and MW estimation of polypeptides that manifest these activities, and for monitoring and control of fungal and bacterial cellulase and xylanase production.